CORRELATION BETWEEN THE INTENSITY OF SMARTPHONE USE AND STRESS LEVELS AMONG STUDENTS OF SMKN 1 PENAJAM PASER UTARA - Rizal Nur Dwi Yanto; Rini Wedhayanti (Faculty of Psychology, Diponegoro University, 2025)
The increasing intensity of smartphone use among adolescents has raised serious psychological concerns globally. Excessive screen exposure—particularly after waking up—can disrupt circadian rhythms, impair sleep quality, and increase stress hormone levels (Zhao et al., 2024). Previous reviews and meta-analyses indicate that prolonged digital engagement correlates with higher stress and depressive symptoms among youth (Paulus et al., 2023; Gao et al., 2024; Yu et al., 2025). This study aimed to analyze the correlation between morning smartphone use intensity and stress levels among vocational high school students in Indonesia. A quantitative cross-sectional method was applied, involving 70 eleventh-grade students of SMKN 1 Penajam Paser Utara selected through purposive sampling. Stress levels were measured using the Depression Anxiety Stress Scales-21 (DASS-21), and data were analyzed using Pearson correlation. Results revealed a significant positive relationship between morning smartphone use and stress levels (r = 0.673, p < 0.001), consistent with prior device-logged findings linking screen exposure to elevated stress and mood dysregulation (Bradley & Howard, 2023). The findings highlight the need for educational programs promoting digital self-regulation and mental health awareness among adolescents. Future studies are encouraged to employ longitudinal or experimental designs with larger samples to explore causal mechanisms and physiological pathways (Zhao et al., 2024).